2006
DOI: 10.1103/physrevlett.97.037201
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Ferromagnetism inZn1xCrxTeDoped with Iodine as ann-Type Dopant

Abstract: The effect of additional doping of charge impurities was investigated in a ferromagnetic semiconductor Zn1-xCrxTe. It was found that the doping of iodine, which is expected to act as an n-type dopant in ZnTe, brought about a drastic enhancement of the ferromagnetism in Zn1-xCrxTe, while the grown films remained electrically insulating. In particular, at a fixed Cr composition of x=0.05, the ferromagnetic transition temperature TC increased up to 300 K at maximum due to the iodine doping from TC=30 K of the und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 17 publications
(19 reference statements)
4
29
0
Order By: Relevance
“…In the case of ZnTe:Cr film, poor crystallinity was observed along with a main peak along (2 0 0) crystallographic direction indicating the ZnCrTe cubic zinc blende structure. This peak is similar to a peak observed by Kuroda et al [24,25] for ZnTe:Cr thin film grown on GaAs (1 0 0) substrate by MBE technique. In addition to the main peak along (2 0 0) crystallographic direction, small peaks were also observed indicating Cr, Cr 2 O 3 and CrTe precipitates [26,27].…”
Section: Microstructuresupporting
confidence: 82%
“…In the case of ZnTe:Cr film, poor crystallinity was observed along with a main peak along (2 0 0) crystallographic direction indicating the ZnCrTe cubic zinc blende structure. This peak is similar to a peak observed by Kuroda et al [24,25] for ZnTe:Cr thin film grown on GaAs (1 0 0) substrate by MBE technique. In addition to the main peak along (2 0 0) crystallographic direction, small peaks were also observed indicating Cr, Cr 2 O 3 and CrTe precipitates [26,27].…”
Section: Microstructuresupporting
confidence: 82%
“…On the other hand, the diffraction pattern of ZnTe:Cr film shows amorphous background along with a main peak along (200) crystallographic direction indicating ZnCrTe cubic zinc blende structure. This peak is similar to a peak observed for ZnCrTe film on GaAs (100) substrate prepared by using MBE technique as observed by Shinji Kuroda et al [17,18]. In the doped sample, in addition to the peak along (200) crystallographic direction indicating ZnCrTe cubic zinc-blende phase, peaks corresponding to Cr related phases such as Cr, Cr2O3 and CrTe are also observed in the amorphous background [19,20].…”
Section: Structural Analysissupporting
confidence: 55%
“…21 Indeed, Saito et al 12,13 found that the Curie temperature ͑T C ͒ in ͑Zn,Cr͒Te could be as high as 300 K and the ferromagnetism was proved by the magnetic circular dichroism ͑MCD͒ that originated from the s, p-d interaction of Cr ions and the ZnTe host. Later, this work was confirmed by Ozaik et al 15,17 Very recently, Ozaik et al 18 studied the carrier doping effect in ͑Zn,Cr͒Te and found that while the ferromagnetism was suppressed by a p-type doping, 16 it was significantly enhanced by a n-type doping. In all of these reports, ͑Zn,Cr͒Te samples were fabricated by molecular beam epitaxy ͑MBE͒, and the transport properties were not studied in detail.…”
Section: Introductionmentioning
confidence: 66%
“…4-8͒ and In 1−x Mn x As. [9][10][11] Various efforts were also focused on transition metal doped II-IV compounds [12][13][14][15][16][17][18][19] and oxides. 20 Especially for Cr or V doped ZnTe, first principles calculation based on the density functional theory predicted an ferromagnetic ground state that is more favorable than the antiferromagnetic or spin-glass state.…”
Section: Introductionmentioning
confidence: 99%